Answer:
fghjk
Step-by-step explanation:
Answer:
6x+3
Step-by-step explanation:
8x +7 - 2x - 4
8x-2x+7-4 ( combine like terms)
answer:
6x+3
Reminder:Whenever combining like terms, the sign changes the same
Hope this helps and make sure to thank me!
Answer: 9
Step-by-step explanation: Here, we have the expression <em>4x - 7</em> and we want to evaluate the expression when <em>x</em> is equal to 4.
To evaluate an expression, we simply plug the value
of the variable into the expression and solve.
So here, since <em>x</em> is equal to 4, we have 4(4) - 7.
4(4) is equal to 16.
So we have 16 - 7 which is equal to 9.
So the value of our expression when <em>x</em> is equal to 4 is 9.
Advertising is x and revenue is y
(0,2)(2,6)
slope = (6 - 2) / (2 - 0) = 4/2 = 2
y = mx + b
slope(m) = 2
(0,2)...x = 0 and y = 2
now we sub and find b, the y int
2 = 2(0) + b
2 = b
so ur equation is : y = 2x + 2
spends 10 mill on advertising.....so x = 10
y = 2x + 2
y = 2(10) + 2
y = 20 + 2
y = 22.....so the revenue (y) of the company is 22 (million)